Chlorhexidine incorporated into the prosthesis as a treatment strategy for denture stomatitis - Marcela Mendes Medeiros Michelon; Karina de Paula Lopes Campos; Luciana Quintanilha Pires Fernandes; Daniel de Moraes Telles; Guaracilei Junior Maciel Vidigal (Associação Brasileira de Odontologia, 2017)
Objective: to perform a literature review on the denture stomatitis (DS) treatment, in order to propose the incorporation of chlorhexidine into the denture as a treatment strategy for DS. Material and Methods: an advanced search was undertaken in MEDLINE/PubMed baseline from 1976 to 2016. Sixty-five papers were retrieved using the following keywords: chlorhexidine, denture stomatitis, denture relining. Of those, 35 papers were directly related to the subject and were therefore selected for a narrative review. Results: DS is an inflammatory reaction of multifactorial etiology, usually associated with Candida albicans and often observed in complete denture wearers. Most treatments rely on patient cooperation. Chlorhexidine (CHX) has antifungal activity and can be incorporated into denture lining materials without causing significant alterations in denture resin structure and without depending on patient compliance. Conclusion: according to the results of in vitro studies, CHX released from denture relining materials may be convenient to reduce denture biofilms and treat DS, but further in vivo studies are necessary to recommend clinical use.